Ambient Pollution–related Reprogramming of the Human Small Airway Epithelial Transcriptome - O’Beirne, Sarah L.; Shenoy, Sushila A.; Salit, Jacqueline; Strulovici-Barel, Yael; Kaner, Robert J.; Visvanathan, Sudha; Fine, Jay S.; Mezey, Jason G.; Crystal, Ronald G. (American journal of respiratory and critical care medicine, 2018)
Epidemiologic studies have demonstrated that exposure to particulate matter ambient pollution has adverse effects on lung health, exacerbated by cigarette smoking. Particulate matter less than or equal to 2.5 μm in aerodynamic diameter (PM ) is among the most harmful urban pollutants and is closely linked to respiratory disease. Based on the knowledge that the small airway epithelium (SAE) plays a central role in the pathogenesis of smoking-related lung disease, we hypothesized that elevated PM levels are associated with dysregulation of SAE gene expression, which may contribute to the development of respiratory disease. From 2009 to 2012, healthy nonsmoker (n = 29) and smoker (n = 129) residents of New York City underwent bronchoscopy with SAE brushing (2.6 ± 1.3 samples/subject; total of 405 samples). SAE gene expression was assessed by Affymetrix HG-U133 Plus 2.0 microarray. New York City PM levels (Environmental Protection Agency data) were averaged for the 30 days before bronchoscopy. A linear mixed model was used to assess PM -related gene dysregulation accounting for multiple clinical and methodologic variables. Thirty-day mean PM levels varied from 6.2 to 18 μg/m . In nonsmokers, there was no dysregulation of SAE gene expression associated with ambient PM levels. In marked contrast, n = 219 genes were significantly dysregulated in association with PM levels in the SAE of smokers. Many of these genes relate to cell growth and transcription regulation. Interestingly, 11% of genes were mitochondria associated. PM exposure contributes to significant dysregulation of the SAE transcriptome of smokers, linking pollution and airway epithelial biology in the risk of development of respiratory disease in susceptible individuals.